The tradition of science : - Bruno, Leonard C. (Library of congress, 1987)
Any real understanding of where we stand scientifically today and where we are headed depends to a great extent on an awareness of how we reached those scientific achievements. The increased impact of science and technology on our lives makes such an understanding even more important. For this reason, this book is intended to provide information about the major works of science in the collections of the Library of Congress. These selected works are organized here by traditional scientific discipline and are treated in historical and, generally, chronological order.